中国银行不良贷款管理浅谈 = Analysis of China banks, unhealthy loans management - 俞 茂根 Yu, Mao Gen (2010)
由于中国经济进入20世纪90年代加大，以市场为取向的改革不断深化在经济的各个方面。经济也变得更加outwardoriented。然而，在银行系统的不良贷款也已积累了大量与中国经济发展和安全也因此受到不利影响。从当前绘画*亚洲的经验金融危机，有效地解决了不良贷款的中国银行系统的问题是完全必要的保证在中国经济从金融危机的偏离。 Since the Chinese economy stepped into 1990s, the market-oriented reform has been deepened in all aspects of the economy. The economy has also become more outwardoriented. However, the bad loans in the banking system has also been accumulated substantially and the economic development and security of China has thus been adversely affected. Drawing the experience from the current*Asian financial crisis, to effectively solve the problem of bad loans in the Chinese banking system is absolutely necessary to ensure the Chinese economy to deviate from financial crisis.